Speech Representations of Unity in Early 20th Century Russian Parliamentary Discourse: A Study of Lexemes ‘Edinstvo’ [Unity] and ‘Edinenie’ [Unification] - S. A. Gromyko (Научный диалог)
The article analyzes the functioning of the lexemes ‘edinstvo’ [unity] and ‘edinenie’ [unification] in the oral public speeches of the deputies of the prerevolutionary State Duma. The aim of the article is to systematize speech representations of the idea of unity on the example of the lexemes ‘edinstvo’ [unity] and ‘edinenie’ [unification] in the Russian parliamentary discourse of the early 20th century in a rhetorical-pragmatic aspect. The category of persuasive complex was used as an instrument for analyzing the persuasiveness of parliamentary discourse. It was established that the analyzed lexemes were actively used in the Russian parliamentary discourse of the early 20th century to express the semantics of integrativeness. Integrativeness, expressed by the analyzed lexemes, relates to many diverse topics, from family and court to opinions, principles, and views. Functional differences between the use of the lexemes ‘edinstvo’ [unity] and ‘edinenie’ [unification] were identified and analyzed. The persuasiveness of ‘edinstvo’ [unity] and ‘edinenie’ [unification] in the rhetorical practice of the prerevolutionary State Duma is associated with achieving a high degree of pathos in speeches through the use of these lexemes in their literal sense, developing epithets with them, and incorporating them into metaphors. It is proven that the use of the lexemes ‘edinstvo’ [unity] and ‘edinenie’ [unification] in a specific context was a political marker, as there is a certain specialization of word usage in speeches by representatives of different political forces.